Sizes at first sexual maturity and capture and demographic parameters of crabs Callinectes amnicola and Cardisoma armatum in the complex “Nokoué lake Porto-Novo lagoon” in South-Benin. - Goussanou, Appolinaire; BONOU, ASSOUAN GABRIEL; CHIKOU, ANTOINE; MENSAH, GUY APOLLINAIRE; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2018)
Crabs Callinectes amnicola and Cardisoma armatum are intensively exploited in the complex Nokoué lake Porto-lagoon in South Benin. This study aims to evaluate the current exploitation level of these species based on the sizes at first sexual maturity and capture as well as on certain demographic parameters. For this, 1287 Callinectes amnicola crabs and 322 Cardisoma armatum crabs were collected, sexed and measured between May 2016 and April 2017. The study revealed that in both crab species, the calculated sex ratios were not different from the theoretical sex ratio (p> 0.05). In crab Callinectes amnicola, the size at first sexual maturity of females was lower than that of males whereas in Cardisoma armatum, males had a size at first sexual maturity inferior to females. The size at the first capture of Callinectes amnicola crab (4.60 cm) was greater than that of the Cardisoma armatum crab (4.41 cm). In both crab species, first-catch sizes were all smaller than first maturity sizes. The growth coefficient and the growth performance index in the crab Cardisoma armatum were superior to those of the crab Callinectes amnicola. The total mortality, natural mortality, and fishing mortality were higher in crab Cardisoma armatum than in crab Callinectes amnicola. In the complex Nokoué lake Porto-Novo lagoon in South Benin, crabs Callinectes amnicola and Cardisoma armatum are overexploited.
Keywords: sexual maturity; growth; mortality; exploitation; Benin